232k views
1 vote
Y = -7x -1
4x - 7y = 7

User IndyStef
by
5.0k points

1 Answer

3 votes

Answer:

(x, y) = (0, -1)

Explanation:

Since we have an expression for y, it is convenient to substitute that into the second equation:

4x -7(-7x -1) = 7

4x +49x +7 = 7

53x = 0

x = 0

Substituting into the first equation gives ...

y = -7ยท0 -1

y = -1

The solution is (x, y) = (0, -1).

Y = -7x -1 4x - 7y = 7-example-1
User Emanuil Rusev
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.